Działania na rzecz redukcji emisji gazów cieplarnianych w województwie lubuskim w latach 2010-2015 = Actions for greenhouse gas emission reductions in the Lubuskie province in the years 2010-2015 - Słobodzian-Ksenicz, Oryna; Jasiewicz, Marzena; Polus, Dominik (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The results of the analysis - using desk research - funding projects in the area of air protection and reduction of GHG emissions in 2010-2015 in Lubuskie. WFOŚiGW and LRPO are the leading financing institutions major investments and carrying out tasks in the area of air protection and reduction of GHG emissions. The result of the investment is increasing the share of renewable energy and reducing emissions of pollutants generated in the processes that generate the largest amount of GHG and their precursors.
Keywords: gazy cieplarniane; redukcja emisji; dofinansowanie; inwestycje proekologiczne; Lubuskie; greenhouse gases; emission reduction; funding; ecological investments; lubuskie voivodeship